Survey of oncohematological pharmaceutical care situation in Spain - María José Martínez-Bautista; Irene Mangues-Bafalluy; Gerardo Cajaraville-Ordoñana; María Josep Carreras-Soler; Ana Clopés-Estela; Estela Moreno-Martínez (Farmacia Hospitalaria)
Objective: To learn about the baseline of Oncohematological Pharmacy Units in Spanish hospitals in order to identify areas for improvement. Method: A survey in line with the objectives set in GEDEFO 2020 Strategic Plan of Pharmaceutical Care for oncohematological patients was designed. The survey was hosted on GEDEFO’s website during March and April 2017. Activity data for 2016 was collected. Results: A total of 95 hospitals responded to the survey. Out of which, 76% had an integrated information system of pharmacotherapeutic process management, where a variability in technological and organizational processes were found. The oncohematological pharmacist led the implementation of the principles of medicine, based on evidence and results obtained in routine clinical practice. It was shown that 88% of hospitals had standardized protocols. As for safety practices, in 83% of hospitals, oncohematological pharmacists actively participated in the development and maintenance of risk management program, implemented to prevent errors. Preparation was centralized in 89% of hospitals. Variability was observed in pharmaceutical care depending on where the patient was attended. In 92% of hospitals, pharmacists served as reference for Oncohematology, although with different levels of training. Major deficiencies were observed in training programs and teaching. Of all oncohematological pharmacists, 53% had been a researcher over the past three years. Conclusions: These results mark the starting point for Spanish Oncohematological Pharmacy Units to develop strategies for improving the quality of pharmaceutical care offered to oncohematological patients and led by GEDEFO, heads of service, and oncohematological patients themselves.